Clinical characteristics, evolution and treatment of pulmonary arterial hypertension at a Peruvian referral hospital - Pariona , Marcos (2022)
Objective: To describe the clinical and epidemiological characteristics, evolution and treatment of patients with pulmonary arterial hypertension.Materials and methods: A descriptive study that included 47 patients with a primary diagnosis of pulmonary arterial hypertension. Results: The average age of the patients was 48 years and 91.49 % were females. The average follow-up was 39 months.The main types of pulmonary arterial hypertension were the one associated with congenital heart diseases (48.93 %), the one associated with connective tissue diseases (21.28 %) and idiopathic hypertension (17.02 %). Monotherapy (mainly with sildenafil) and sequential combination therapy (sildenafil plus bosentan) were used in 78.72 % and 21.28 % of the patients,respectively. During the follow-up, 70.21 % of the patients were hospitalized at least once and five patients died, resulting in a cumulative total mortality of 10.64 %. Conclusions: Pulmonary arterial hypertension predominantly affects young people and females. The main associated etiology is congenital heart disease. The most frequently used specific treatment is sildenafil monotherapy. The mortality rate was lower than that reported in other studies.